Les yeux de la langue, l’oreille des images de Nelly Kaplan. Et quoi de l’érotique ? - Mireille Calle-Gruber (Itinéraires)
Nelly Kaplan, movie-maker and writer with close affinities with the Surrealists, organizes her work on the interweaving of genres and tonalities, humor and eroticism. Neither a feminist nor a misogynist nor a man-hater, she puts forth an “androgynous creation”: neither masculine nor feminine both masculine and feminine. We shall see that textual body and sexual body cannot be dissociated and that literary genres always have to do with the inscription of gender. What will thus be at stake will be to take full account of the impact of the word genre in its designation in the French language: grammatical genre, biological genre and sexual genre, literary genre, artistic genre. And to assess the work of the art-forms that it entails. Detour through quotations, quantum-novel and panic-writing are thus some of the forms that will be examined in Nelly Kaplan’s literary production, and that elaborate more than a poetics: an erotics.